4+6x=18-(2-2x)

Simple and best practice solution for 4+6x=18-(2-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+6x=18-(2-2x) equation:


Simplifying
4 + 6x = 18 + -1(2 + -2x)
4 + 6x = 18 + (2 * -1 + -2x * -1)
4 + 6x = 18 + (-2 + 2x)

Combine like terms: 18 + -2 = 16
4 + 6x = 16 + 2x

Solving
4 + 6x = 16 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
4 + 6x + -2x = 16 + 2x + -2x

Combine like terms: 6x + -2x = 4x
4 + 4x = 16 + 2x + -2x

Combine like terms: 2x + -2x = 0
4 + 4x = 16 + 0
4 + 4x = 16

Add '-4' to each side of the equation.
4 + -4 + 4x = 16 + -4

Combine like terms: 4 + -4 = 0
0 + 4x = 16 + -4
4x = 16 + -4

Combine like terms: 16 + -4 = 12
4x = 12

Divide each side by '4'.
x = 3

Simplifying
x = 3

See similar equations:

| 3b^2-40=-196 | | X+1+7=4 | | -5x+(-4-9)=6 | | -5p=2p-35 | | 2(6-x)=2 | | -14+x=-32 | | (x-6y)(5x+6y)=0 | | 3y+x=0 | | (8x-3)-(4x-8)= | | 5x-25=2(2x+3) | | -3-3y=-15x | | y+1=3(0-2) | | 35-x=-8-3(1+8x) | | 3x+2=5x-24 | | 17=4(a-2)+2 | | 6*g=9 | | 2x^2+27x-8.7=0 | | Y-2-x=0 | | 32x+32=27x | | -11-3x=10-4x | | 4(8-x)=16 | | 5x-(2.2x+8)= | | 74/22200= | | -6=2h-10 | | 8-0(9+0)= | | -5+8=72 | | m-3.41=10.7 | | 3=-y | | Y-3=3.2(x-1) | | 22200/74= | | -18+24+(-13)+(-19)= | | -3y+3x=6 |

Equations solver categories